2017
DOI: 10.4269/ajtmh.17-0167
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clinical and Subclinical Plasmodium falciparum and Plasmodium vivax Malaria in Two Remote Rural Communities on the Myanmar–China Border

Abstract: Abstract.Malaria infections may be symptomatic, leading to treatment, or “asymptomatic,” typically detected through active surveillance, and not leading to treatment. Malaria elimination may require purging both types of infection. Using detection methods with different sensitivities, we conducted a cross-sectional study in two rural communities located along the border between China’s Yunnan Province and Myanmar’s Shan and Kachin States, to estimate the prevalence of asymptomatic and symptomatic malaria. In M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
3
21
5
Order By: Relevance
“…Using microscopy in the current study, the overall prevalence of malaria was lower compared to RDT. is is consistent with recent studies by Sumari et al [11] and Huang et al [21] but contrary to results of a study in Myanmar where microscopy produced a higher prevalence than RDT [22]. e microscopic prevalence found in this current study is far lower than the 56% reported in 2010 and 27.5% in 2017 during a similar dry season study in the northern part of Ghana [18,23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using microscopy in the current study, the overall prevalence of malaria was lower compared to RDT. is is consistent with recent studies by Sumari et al [11] and Huang et al [21] but contrary to results of a study in Myanmar where microscopy produced a higher prevalence than RDT [22]. e microscopic prevalence found in this current study is far lower than the 56% reported in 2010 and 27.5% in 2017 during a similar dry season study in the northern part of Ghana [18,23].…”
Section: Discussionsupporting
confidence: 91%
“…Evaluation of gender as a biological factor in asymptomatic malaria is, however, beyond the scope of this present study and therefore recommended for further studies. Nevertheless, in Myanmar, Huang et al [21] and Zaw et al [22] separately reported a higher parasite prevalence among asymptomatic males. Likewise, Kiemde et al [25] found asymptomatic malaria to be prevalent among males using both microscopy and RDT.…”
Section: Discussionmentioning
confidence: 97%
“…A few studies of the entomological determinants of malaria transmission in the same areas as this study along the Thai–Myanmar border also reported that Anopheles mosquitoes exhibited an outdoor and early biting pattern with active timing between 06:00 and 07:00 [ 53 , 54 ]. Several studies have reported high malaria morbidity among children [ 55 , 56 ]; interestingly, one study in the Laiza refugee camp along the Myanmar–China border [ 57 ] speculated that daytime malaria transmission might occur near the primary school attended by younger children. It would be interesting to conduct an entomological investigation to explore this hypothesis in Tha-Song-Yang District.…”
Section: Discussionmentioning
confidence: 99%
“…DF is still one of the major tropical diseases and an increasing threat to public health in the world [7,8], but the impact of dengue on local public health is still being neglected now. While extensive investigations about malaria have been done in the KSR2, Myanmar [2,3,[9][10][11][12][13][14][15][16][17][18], studies on DF are still unavailable.…”
Section: Introductionmentioning
confidence: 99%